2014
DOI: 10.1242/jcs.145318
|View full text |Cite
|
Sign up to set email alerts
|

Zinc efflux through lysosomal exocytosis prevents zinc-induced toxicity

Abstract: Zn2+ is an essential micronutrient and an important ionic signal whose excess, as well as scarcity, is detrimental to cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 66 publications
3
75
0
Order By: Relevance
“…Further studies then indicated that lysosomes and their networks might represent a special detoxification mechanism for transition metal toxicity [30]. Our current findings concur with this view, but also indicate the likely involvement of melanosomes in these circumstances.…”
Section: Discussionsupporting
confidence: 88%
“…Further studies then indicated that lysosomes and their networks might represent a special detoxification mechanism for transition metal toxicity [30]. Our current findings concur with this view, but also indicate the likely involvement of melanosomes in these circumstances.…”
Section: Discussionsupporting
confidence: 88%
“…However, several possibilities exist that may explain this finding. First, since the D 103 E variant was associated with lysosomes, Zn efflux could occur via non-classical lysosomal-mediated pathways [30]. As an alternative explanation, although ZnT1 expression was reduced, the rate of ZnT1-mediated Zn efflux may have been increased by intrinsic factors like pH and calcium [31].…”
Section: Genetic Variation In Slc30a2 Is a Major Modifier Of Milk [Zn]mentioning
confidence: 99%
“…We also used bafilomycin to raise cytosolic Zn 2+ ( Fig. S3F) by inhibiting lysosomal sequestration of the ion (Kukic et al, 2014). Again, this manoeuvre caused loss of stress fibres and appearance of filopodia (Fig.…”
Section: +mentioning
confidence: 99%